Pengembangan Instrumen Qamariyah Syamsiyah Moon Phase Detector (QaSyM PD) dengan Penanggalan Sepanjang Masa: Indonesia - Annisa Nurfadilah; Syarif, Rasyawan; Fatmawati (HISABUNA: Jurnal Ilmu Falak, 2024)
This article discusses the Development of Qamariyah Shamsiyah Moon Phase Detector (QaSyM PD) Instrument with All-Time Dating. The problem formulations in this thesis are 1) How is the QaSyM PD Instrument in determining the phases of the moon in Qamariyah and Shamsiyah, 2) How the Development of QaSyM PD Instrument can be valid for all time. This study uses Research and Development (RnD) research which means development research in this case the instrument by adopting the 4 D model namely Define, Design, Developing, and Dissemination. The results of this study indicate that the QaSyM PD Instrument with innovations made by researchers in the development of its dating can be valid for all time. With several stages that change the layers of the instrument starting from the first layer of the Shamsiyah calendar (Gregorian Calendar), the second layer of the Qamariyah Calendar (Hijriyah Calendar) and the third layer of moonrise and sunset times. The development of the QaSyM PD Instrument was carried out with validation and testing stages carried out through supporting data and applications. So as to produce an instrument that is valid for all time. The implication of this research is that this instrument is expected to make an educational contribution to the community, especially those who are unfamiliar with Falak Science. This research also has implications for the development of technology and science in the field of Falak Science and astronomy which can encourage further research to understand the motion of the moon with a simpler system.